Navīsanda-yi Rustam al-tawārīkh kīst? : va pizhūhishī dar nigāh-i ū bih Īrān - Nūḏarī, Jalalī (Miras Maktoob, ISBN: 9789004365452., 2019)
In literary criticism, the blending of historical fact and literary invention is often referred to as 'fictionalized history'. While the main characters and episodes are largely based on historical record, in works of this kind, the author takes the liberty to invent or manipulate thoughts, dialogues, or events. Gore Vidal's Lincoln or Robert Graves' I, Claudius are modern examples of fictionalized history. In early Persian literature, Firdawsī's (d. 411/1020) Shāh-nāma is a fine specimen of fictionalized history. Rustam al-ḥukamā's (19th century) Rustam al-tawārīkh pretends to be an historical work, covering the last days of the Safavid era from the beginning of the rule of Shāh Sulṭān Ḥusayn (r. 1105-35/1694-1722), until the death of Fatḥ ʿAlī Shāh Qājār (d. 1249/1834). In this critical study, Jalīl Nudharī argues that Rustam's work is fictionalized history rather than history, and that Rustam al-ḥukamā is an alias of the well-known nineteenth-century writer Riḍā Qulī Khān Hidāyat (d. 1871)